KEMANDIRIAN DAN EFEKTIVITAS DALAM MELAKSANAKAN OTONOMI DAERAH KABUPATEN DAN KOTA DI PROVINSI KALIMANTAN SELATAN - MUHAMMAD FAISAL PERDANA PUTERA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of this study is to examine the performance of regional finance at the district and municipal governments in South Kalimantan province based on the independence and effectiveness of regional finance period 2012 to 2016 as well as the trend of regional financial effectiveness and effectiveness period 2012 to 2016. Type of research used is descriptive, Regency and City in South Kalimantan Province and the sample of all districts and cities in South Kalimantan Province. Secondary data were obtained from Regional Finance Board of South Kalimantan Province and Directorate General of Balance of Ministry of Finance. Analytical techniques used are the ratio of independence and local financial effetivity as well as percentage trend of independence and effectiveness of regional finance.The results obtained in this study are: 1) The ratio of regional autonomy in general in 2012 to 2016 into very low category. 2) The effectiveness ratio of regional finance in general from 2012 to 2016 is effective except the Upper River Central Regency is in a balanced category 3) The trend of regional autonomy has a good development unless the Regency of Banjar in 2015 and 2016 is below 100 percent. 4) Trend of regional financial effectiveness in the year 2013 until 2016 tend to positive trend there are 4 area and that tend to experience negative trend direction there are 8 area.Keywords: Independence, Effectiveness, Regional Autonomy